Enhancing Language Literacy for the Children of Rejatengah Village to Achieve Indonesia's Golden Generation in 2045 - Donny Adiatmana Ginting; Fernando De Napoli Marpaung; Rosmen Rosmen; Yunita Sari Adelina; Muhammad Hassan (Lembaga Pengembangan Kinerja Dosen, 2025)
This article explores a community service initiative aimed at enhancing literacy among children in Rejatengah Village, Indonesia, as part of the national effort to develop Indonesia’s Golden Generation by 2045. The project was conducted by a team from Al Maksum College of Teacher Training and Education over a one-month period, targeting children aged 6 to 9 years. The initiative involved comprehensive educational activities, including literacy assessments, interactive workshops, and parental involvement, to foster a supportive learning environment. Significant improvements in literacy skills were observed, attributed to the innovative teaching methods and community engagement strategies employed. The establishment of a permanent educational resource center has ensured the sustainability of educational efforts, serving as a model for similar interventions in other rural areas. This project not only highlights the critical role of community-based educational programs in enhancing literacy but also demonstrates the potential of such initiatives to contribute to broader national development goals.